2018
DOI: 10.21294/1814-4861-2018-17-3-41-50
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the Tp53 Gene in Patients With Gastric Cancer in Prospective and Clinical Case-Control Studies

Abstract: Background.A functionally significant TP53Arg72Pro polymorphism can contribute to the development of gastric cancer (GC).The aim:to study the associations of genotypes and alleles of the TP53Arg72Pro 4 polymorphism with GC and biomarkers of gastric ucosal atrophy in population-based prospective and case-control clinical trials among the population of Siberia.Material and methods.As a part of the epidemiological study, data of the international multicenter HAPIEE project for 2003–05, based on a population sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It has been shown that their carriers are more likely to suffer from liver diseases [16] and have an increased risk of tuberculosis [15,17]. Allele -174G is considered a risk factor for squamous cell lung cancer and chronic obstructive pulmonary disease [18], cancer and fundic atrophy of the stomach [19], ovarian cancer [20], intrauterine infection of the fetus [21], development of cerebral arteriovenous malformation [22] and is associated with the risk of developing type 2 diabetes [23,24]. Allele -572С has also been associated with ischemic stroke in indigenous West African men [25].…”
mentioning
confidence: 99%
“…It has been shown that their carriers are more likely to suffer from liver diseases [16] and have an increased risk of tuberculosis [15,17]. Allele -174G is considered a risk factor for squamous cell lung cancer and chronic obstructive pulmonary disease [18], cancer and fundic atrophy of the stomach [19], ovarian cancer [20], intrauterine infection of the fetus [21], development of cerebral arteriovenous malformation [22] and is associated with the risk of developing type 2 diabetes [23,24]. Allele -572С has also been associated with ischemic stroke in indigenous West African men [25].…”
mentioning
confidence: 99%